Seed-borne and seed-transmitted fungi, etiological agents of damping-off of castor bean - Lima, Emídio Ferreira; Batista, Fernando Antônio Souto; Santos, José Wellington dos (Pesquisa Agropecuaria Brasileira, 1997)
Castor bean (Ricinus communis L.) is susceptible to more than 150 different microorganisms and is affected by several diseases some of which responsible for great economic harms. The purpose of this study was to detect seed-transmitted fungi and to identify those pathogenics to this crop. It was made seed health analysis and pathogenicity studies with the microorganisms detected under laboratory conditions, in Campina Grande, PB, Brazil. Several fungi were detected in castor seed. Some are causal agents of serious plant diseases. Fusarium sp., Alternaria ricini, Aspergillus flavus and Chaetomium sp. caused seed rot and or lower germination. Fusarium sp., Rhizoctonia solani and Alternaria ricini were transmitted by seed and caused severe seedling damping-off.